Embryonic developmental process governing the conspicuousness of body stripes and blue tail coloration in the lizard Plestiodon latiscutatus. Issue 1 (23rd November 2016) - Kuriyama, Takeo; Hasegawa, Masami
SUMMARY: The combination of body stripes and vivid blue tail color has independently evolved in different lizard families. To understand how and when lizards developed this coloration, we microscopically compared the embryonic development of pigment cells in two island populations of Plestiodon latiscutatus that exhibit either striped and blue tailed or inconspicuously striped and blue tailed juveniles, based on the newly determined 12 normal developmental stages of embryos from shortly after egg laying to just before hatching. We focus on the role of the melanophores in the body stripe and the role of iridophore morphotypes in the extent of blue tail coloration. The melanophore density in the black background region was higher in lizards with vivid stripes than in lizards with drab stripes. Iridophores started to fill the dermal space that was not yet occupied by melanophores, which resulted in a higher iridophore density in stripes than in the inter‐stripe regions. We also discovered that iridophores with thin platelets reflecting blue structural coloration appeared at a specific region in the tail at stage 11. The position of the tail where iridophores emerged coincided with the boundary area separating anterior brown and green colored tail from posterior blue colored tail after hatching.